Neutrophils-related host factors associated with severe disease and fatality in patients with influenza infection - Benjamin M. Tang (Nature Portfolio, 2019)
Identification of host factors associated with severe influenza infection could provide insights into treatment options. Here, the authors provide transcriptomic analyses of blood from >100 influenza infected patients and show that changes in circulating neutrophils are associated with severe influenza infection.